2009
DOI: 10.1371/journal.pone.0006139
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gene Expression in Actinobacillus pleuropneumoniae Exposed to Bronchoalveolar Fluid

Abstract: Background Actinobacillus pleuropneumoniae, the causative agent of porcine contagious pleuropneumonia, is an important pathogen of swine throughout the world. It must rapidly overcome the innate pulmonary immune defenses of the pig to cause disease. To better understand this process, the objective of this study was to identify genes that are differentially expressed in a medium that mimics the lung environment early in the infection process.Methods and Principal FindingsSince bronchoalveolar lavage fluid (BALF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 107 publications
(109 reference statements)
0
39
0
Order By: Relevance
“…In addition, in a few cases, genes regulated by Epi and NE were the same as those found to be regulated under iron-restriction [53], after bronchoalveolar fluid exposure [45] and during acute infection [32]. There were only a few genes in common that were differentially regulated in the three latter studies.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, in a few cases, genes regulated by Epi and NE were the same as those found to be regulated under iron-restriction [53], after bronchoalveolar fluid exposure [45] and during acute infection [32]. There were only a few genes in common that were differentially regulated in the three latter studies.…”
Section: Discussionmentioning
confidence: 58%
“…*Genes previously identified as being relevant for A. pleuropneumoniae infection [11], [18], [20], [21].aLocus numbers from A. pleuropneumoniae serotype 5 (L20) or alternatively, if gene could not be identified in serotype 5, then from A. pleuropneumoniae serotype 3.bFunction of genes according to Clusters of Clusters of Orthologous Groups of proteins (COGs). C: energy production and conversion; G: carbohydrate transport and metabolism; H: coenzyme transport and metabolism; O: posttranslational modification, protein turnover, chaperones; P: inorganic ion transport and metabolism; R: general function prediction, only; S: function unknown.…”
Section: Resultsmentioning
confidence: 99%
“…We observed in vivo activation of oxidative stress resistance mechanisms, represented by the two genes coding for thiol peroxidase ( tpx ) and cytochrome c peroxidase ( ccp ), respectively, both involved in protecting the bacteria against hydrogen peroxide [49]. In A. pleuropneumoniae grown in bronchoalveolar fluid, ccp has earlier been found to be among the most highly up-regulated genes [21]. Also, it has been reported that the lipid hydroperoxide peroxidase, encoded by tpx , protects Salmonella enterica from hydrogen peroxide stress in vitro and facilitates intracellular growth [50].…”
Section: Resultsmentioning
confidence: 99%
“…These genes are thought to be regulated in the host environments encountered by the pathogen, such as conditions of iron-deficiency or a limited number of anaerobic or branched chain amino acids (BCAA) (Baltes and Gerlach, 2004;Wagner and Mulks, 2006;Deslandes et al, 2007Deslandes et al, , 2010Wagner and Mulks, 2007;Lone et al, 2009). For A. pleuropneumoniae, the up-regulation of many genes has been reported in vivo (Fuller et al, 1999;Deslandes et al, 2010).…”
mentioning
confidence: 99%
“…For A. pleuropneumoniae, the up-regulation of many genes has been reported in vivo (Fuller et al, 1999;Deslandes et al, 2010). At first, ApxIV was detected only in vivo, but recently its expression was discovered in vitro following its addition to broncho-alveolar lavage fluid (BALF) (Lone et al, 2009). Although ApxIV was identified nearly a decade ago, its role in virulence and infection remain unclear (Schaller et al, 1999).…”
mentioning
confidence: 99%